Implanted Layer Characterization - Adharul Muttaqin; Irman Idris (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2007)
In modern semiconductor process technology, ion implantation has become the most important technique to introduce dopant atoms into semiconductor materials. The main advantage of ion implantation technique is its high controllability of process parameters, which influencing dopant distribution profile. This research was intended to characterize the product of ion implantation machine NV-3204.Ion implantation characterization successfully produced and evaluated pn-junction diode characteristics. PN-junction diode was fabricated using 100 keV energy and 5x1013 cm-3 dose of phosphorus on a silicon wafer type N<111>. For all measured area, pnjunction diode has junction depth Xj = 1 um, breakdown voltage -45V, built-in voltage 0.8V, and dopant concentration 5x1018 cm-3. Comparing the simulation, this result exhibited that output of ion implantation machine was well controlled.